Gp96 Peptide Antagonist gp96-II Confers Therapeutic Effects in Murine Intestinal Inflammation - Nold-Petry, Claudia A.; Nold, Marcel F.; Levy, Ofer; Kliger, Yossef; Oren, Anat; Borukhov, Itamar; Becker, Christoph; Wirtz, Stefan; Sandhu, Manjeet K.; Neurath, Markus; Dinarello, Charles A. (Frontiers in Immunology, 2017)
ABSTRACT Background: The expression of heat shock protein gp96 is strongly correlated with the degree of tissue inflammation in ulcerative colitis and Crohn’s disease, leading us to the hypothesis that inhibition of expression via gp96-II peptide prevents intestinal inflammation. Methods: We employed daily injections of gp96-II peptide in two murine models of intestinal inflammation, the first resulting from five daily injections of IL-12/IL-18, the second via a single intra-rectal application of TNBS (2,4,6-trinitrobenzenesulfonic acid). We also assessed the effectiveness of gp96-II peptide in murine and human primary cell culture. Results: In the IL-12/IL-18 model, all gp96-II peptide treated animals survived until day 5, whereas 80% of placebo-injected animals died. Gp96-II peptide reduced IL-12/IL-18-induced plasma IFNγ by 89%, IL-1β by 63%, IL-6 by 43% and TNF by 70% compared to controls. The clinical assessment Disease Activity Index (DAI) of intestinal inflammation severity was found to be significantly lower in the gp96-II treated animals when compared to vehicle injected mice. Gp96-II peptide treatment in the TNBS model limited weight loss to 5% on day 7 compared with prednisolone treatment whereas placebo-treated animals suffered a 20% weight loss. Histological disease severity was reduced equally by prednisolone (by 40%) and gp96-II peptide (35%). Mice treated with either gp96-II peptide or prednisolone exhibited improved endoscopic scores compared with vehicle-treated control mice: vascularity, fibrin, granularity, and translucency scores were reduced by up to 49% by prednisolone and by up to 30% by gp96-II peptide In vitro, gp96-II peptide reduced TLR2-, TLR4- or IL-12/IL18-induced cytokine expression in murine splenocytes, with declines in constitutive IL-6 (54%), LPS-induced TNF (48%) and IL-6 (81%), and in Staphylococcus epidermidis (St. epi.)-induced TNF (67%) and IL-6 (81%), as well as IL-12/IL-18-induced IFNγ (75%). Gp96-II peptide reduced IL 1β, IL-6, TNF, and GM-CSF in human peripheral blood mononuclear cells (PBMC) to a similar degree without affecting cell-viability, whereas RANTES, IL-25, and MIF were 2-3-fold increased. Conclusion: Gp96-II peptide protects against murine intestinal inflammation by regulating inflammation in vivo and in vitro, pointing to its promise as a novel treatment for inflammatory bowel disease.